Efek Self-Efficacy terhadap Readiness for Change Masyarakat Samosir dalam Menyambut Bali Baru - Wilbert; Christine Tandriani; Winnie Gozali; Rianda Elvinawaty (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
To improve Indonesian tourism, The Indonesian Government have launched the New Bali program where Lake Toba with the support of Samosir Island be prioritized to become New Bali. However, there have been some issues that happen, the problem is about the Human Resource problem where the behaviour of people in Samosir Island show that they are still not ready to change into New Bali. There are some factors that influence readiness for change, where one of them is self-efficacy. To find out the truth of whether or not there is a relationship between the two variables, based on data from 383 people of Samosir Island and using descriptive quantitative methods, this study aims to see if there is a relationship and how much contribution between self-efficacy to readiness for change in people of Samosir Island. The data obtained using the scale will be tested using Pearson Product Moment Correlation through the help of IBM SPSS Statistics 22 to test the hypothesis that the results of the study showed that hypothesis is accepted it means that there is a positive relationship between self-efficacy and readiness for change